Pencil beam scanning proton therapy for the treatment of craniopharyngioma complicated with radiation-induced cerebral vasculopathies: A dosimetric and linear energy transfer (LET) evaluation. (August 2020) - Bolsi, Alessandra; Placidi, Lorenzo; Pica, Alessia; Ahlhelm, Frank J.; Walser, Marc; Lomax, Antony J.; Weber, Damien C.
Highlights: Vascular toxicity in craniopharyngioma pediatric cases after proton therapy was evaluated considering dosimetry and LET. Two cases out of 16 pediatric patients presented with RICV. Vascular toxicity was found only for patients treated with asymmetric field arrangements. High max and average LET values were found for vascular toxicity areas identified on MRI for patients with RICV. Abstract: Background and purpose: This study analyses the dosimetric and dose averaged Linear Energy transfer (LETd) correlation in paediatric craniopharyngioma (CP) patients with and without radiation-induced cerebral vasculopathies (RICVs) treated with pencil beam scanning (PBS) proton therapy (PT). Material and methods: We reviewed a series of 16 CP patients treated with PT to a median dose of 54 Gy(RBE). Two (12.5%) index patients presented RICVs 14 and 24 months (median, 19) after PT. Organs at risks (OARs) as bilateral internal carotid arteries (ICAs) and circle of Willis were contoured based on CTs and MRIs pre- and post-PT. Dosimetry was reviewed and LETd distributions were calculated; LETd metric for PTVs and OARs were analysed. For a sub-cohort, dosimetric and LETd values robustness due to range uncertainties were computed. Results: For the two index patients, no correlation was observed between RICVs and OARs doses. However for those patients mean( maximum ) LETd values in the affected OARs were up to 4.0 ± 0.4 ( 7.8 ± 0.1 )keV/μm; those LETd values were significantly higher ( p  = 0.02) than the mean( maximum ) LETd values for the rest of the cohort (mean: 3.1 ± 0.3, maximum: 4.8 ± 1.0  keV/μm). This was due to asymmetric field arrangement, thus resulting in marked asymmetric LETd distributions. For such arrangement, maximum LETd values variations in vascular structures due to range uncertainties were up to 1.2 keV/μm, whilst for the symmetric one they were up to 0.7 keV/μm. Conclusions: For children with and without RICVs, quantitative analysis showed a significant correlation with LETd average/maximum values in vascular structures, whilst no correlation was found on dosimetric parameters.